Alkaline Anion‐Exchange Membranes Containing Mobile Ion Shuttles. Issue 18 (11th March 2016) - Ge, Xiaolin; He, Yubin; Guiver, Michael D.; Wu, Liang; Ran, Jin; Yang, Zhengjin; Xu, Tongwen
Abstract : A new class of alkaline anion‐exchange membranes containing mobile ion shuttles is developed. It is achieved by threading ionic linear guests into poly(crown ether) hosts via host–guest molecular interaction. The thermal‐ and pH‐triggered shuttling of ionic linear guests remarkably increases the solvation‐shell fluctuations in inactive hydrated hydroxide ion complexes (OH − (H2 O)4 ) and accelerates the OH − transport.